Pharmacology and Therapeutics - Joghi Thatha Gowder, Sivakumar (IntechOpen, 2014)
The book "Pharmacology and Therapeutics" targets every aspect of the mechanisms for the chemical actions of both traditional and novel drugs. This book covers six sections: Molecular Modeling and Bio-molecular Pharmacology, Immunopharmacology, Environmental Pharmacology and Toxicology, Nanotechnology and Chemotherapy, Drugs and Drug Delivery System and Addiction Pharmacology. Each of these sections is interwoven with the theoretical aspects and experimental techniques of physiology, biochemistry, nutrition, cellular and molecular biology, microbiology, immunology, genetics, and pathology. This book will be a significant source to scientists, physicians, health care professionals and students who are interested to explore the effect of chemical agents on human life.